Strategic Landscape in Higher Education: A Decadal Bibliometric Analysis of Competitive Dynamics (2013-2023) - Riske Faldesiani; Agus Rahayu; Heny Hendrayati (Universitas Pendidikan Indonesia (UPI), 2024)
This study aims to review the literature on competitive dynamics in Higher Education Institutions (HEIs). The method used in this study is the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) through a bibliometric approach with computational mapping analysis using VOS Viewer. The study period used as literature data material is articles and conference papers indexed in Scopus from 2013 to 2023. The keywords used were